Analysis of self-confidence with Ta’lim Muta’allim values based on Islamic student’s career choices - Suhartiwi, Suhartiwi; Zainul Majdi, Muhammad; Takiuddin, Muhamad; Arianti, Baiq Desi Dwi; Ridwan, Ridwan (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
This study investigates the influence of self-confidence, cultivated through the internalization of Ta’lim Muta’allim values, on students' career choices. Ta’lim Muta’allim values, emphasizing discipline, respect, and the pursuit of knowledge, are hypothesized to significantly contribute to the development of students' self-confidence, a crucial determinant in career decision-making. The research aims to analyze how self-confidence, fostered by these values, impacts students' career preferences and pathways. A quantitative descriptive method was employed, with a sample of 242 students from Madrasah Aliyah Muallimat NW Pancor, Lombok, selected through purposive sampling. Data were collected using a questionnaire assessing self-confidence in the context of Ta’lim Muta’allim values and a career choice survey. Data were analyzed using descriptive statistics and the Kruskal-Wallis Test with the JASP application. Results indicate that students' self-confidence levels were generally high and moderate, influenced by Ta’lim Muta’allim values. Furthermore, no significant differences in self-confidence levels were found across different career choices. Among the nine career choice categories, the average self-confidence level of students was high, with some categories, such as business and finance and diplomacy and governance, falling within the moderate range. In conclusion, this study provides valuable insights into how Ta’lim Muta’allim values, by enhancing self-confidence, play a crucial role in shaping students' career trajectories.